REVIEW OF SOME ASPECTS OF BUSINESS LAW IN BUSINESS FEASIBILITY STUDY - Henry Kristian Siburian (International Journal of Social Science, 2022)
A factor that affects business effectiveness is related to the ability of business institutions to adapt to factors or the prevailing business law system, such as regarding aspects of licensing, legality of business objects, industrial relations, and others. The stages of research carried out in this study are: Data Collection, Data Analysis, Data Development, Data Implementation and Report Generation. The results of this study are Business Law means Business Law and Business Law is a Rule of Game